Pengaruh Self-Regulation terhadap Motivasi Lulus Tepat Waktu pada Mahasiswa Tata Rias dan Kecantikan Universitas Negeri Padang - Theresia Anggiana Sitanggang; Prima Minerva (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study addresses the issue of Cosmetology and Beauty students failing to complete their studies on schedule. It investigates the influence of self-regulation on the motivation to graduate on time, employing a quantitative, causal-associative method. A sample of 90 respondents was selected from the total population. Data analysis involved reliability, validity, and chi-square tests. The findings reveal that 47% of students demonstrated a moderate level of self-regulation, while 41% showed a moderate level of motivation to graduate on time. The chi-square test confirmed the influence of self-regulation on the motivation to graduate on time. Consequently, the study concludes that self-regulation is a crucial factor in the motivation to graduate on schedule. Students are therefore advised to enhance their self-regulation skills—such as goal setting, time management, monitoring academic progress, and self-control—throughout their studies. Additionally, the study program is encouraged to provide support through academic coaching, guidance, and mentoring initiatives designed to strengthen students' self-regulation and thereby boost their motivation to graduate on time.